2017
DOI: 10.1016/j.jnutbio.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for serum 24,25-dihydroxyvitamin D and the ratio with 25-hydroxyvitamin D established using a newly developed LC–MS/MS method

Abstract: 24,25(OH)D is the product of 25(OH)D catabolism by CYP24A1. The measurement of serum 24,25(OH)D concentration may serve as an indicator of vitamin D catabolic status and the relative ratio with 25(OH)D can be used to identify patients with inactivating mutations in CYP24A1. We describe a LC-MS/MS method to determine: (1) the relationships between serum 24,25(OH)D and 25(OH)D; (2) serum reference intervals in healthy individuals; (3) the diagnostic accuracy of 24,25(OH)D measurement as an indicator for vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 38 publications
4
75
0
1
Order By: Relevance
“…Interassay coefficients of variation were <10% for both 25OHD 2 and 25OHD 3 , and the sum of these analytes is reported here. The 25OHD metabolite, 24,25‐dihydroxyvitamin D, was also measured by tandem mass spectrometry using a prior delipidation procedure to maximize recovery . Overnight fasted blood samples collected at each visit were stored at –80°C, and each participant's complete set was batched together before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Interassay coefficients of variation were <10% for both 25OHD 2 and 25OHD 3 , and the sum of these analytes is reported here. The 25OHD metabolite, 24,25‐dihydroxyvitamin D, was also measured by tandem mass spectrometry using a prior delipidation procedure to maximize recovery . Overnight fasted blood samples collected at each visit were stored at –80°C, and each participant's complete set was batched together before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The 25(OH)D is one metabolite of the vitamin D pathway. Tang et al () have reported that measurement of serum 24,25(OH) 2 D can be used as a predictor of vitamin D status. Therefore, the reduced levels of 24,25(OH) 2 D in the skeletal muscle of DHEA mice may imply the decreased vitamin D levels in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although 1,25(OH) 2 D 3 is primarily considered a regulator of calcium metabolism, almost all nucleated cells have vitamin D receptors (Mellanby, 2016) and receptor activation regulates gene transcription and affects cell proliferation, cell differentiation, and formation of proteins that impact cell phenotype (Garg, Rosella, Lubel, & Gibson, 2013; Teixeira et al, 2012; Zendehdel & Arefi, 2019). Thus, 1,25(OH) 2 D 3 affects a wide range of physiological processes including immunological, cardiovascular, and neoplastic diseases (Fox et al, 2019; Jones, 2008; Mellanby, 2016; Tang et al, 2017). Marmosets have higher serum levels of 1,25(OH) 2 D 3 than rhesus and humans (Shinki et al, 1983; Takahashi et al, 1985; Ziegler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of 25(OH)D 3 in marmosets have been measured with radioimmunoassay (RIA) and liquid chromatography–tandem mass spectrometry (LC–MS; Bosseler et al, 2018; Ziegler et al, 2015). LC–MS is able to differentiate vitamin D 2 from D 3 and to measure all vitamin D metabolites (Tang et al, 2017; Ziegler et al, 2015). There have been limited evaluations of 1,25(OH) 2 D 3 in marmosets; most studies report 25(OH)D 3 (Shinki et al, 1983; Takahashi et al, 1985).…”
Section: Introductionmentioning
confidence: 99%